2009
DOI: 10.2174/1874241600902010001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Angiogenic Factors for Predicting Preeclampsia: sFlt-1, PlGF, and Soluble Endoglin~!2008-08-29~!2008-12-15~!2009-01-02~!

Abstract: Preeclampsia is a devastating multisystem syndrome and is a major cause of maternal, fetal and neonatal morbidity and mortality. Angiogenic factors contribute to the molecular mechanisms of preeclampsia and its main phenotypes such as hypertension and proteinuria. Very recently, novel anti-angiogenic proteins including soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng), and one pro-angiogenic protein placental growth factor (PlGF) have been found to be significantly abnormal several weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 62 publications
1
15
0
1
Order By: Relevance
“…4 Other even earlier markers that have investigated include soluble endoglin (sEng), pregnancy-associated plasma protein-A (PAPP-A) and placental protein 13 (PP13). 5,6 Khalil and colleagues originally suggested that PP13 was effective in the first trimester marker; however, in a second larger study, PP13 concentrations were not able to predict pre-eclampsia risk until 13 weeks. 7,8 Unfortunately, several studies have suggested that maladaptive trophoblast invasion may already have committed a pregnancy's fate as early as 11 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…4 Other even earlier markers that have investigated include soluble endoglin (sEng), pregnancy-associated plasma protein-A (PAPP-A) and placental protein 13 (PP13). 5,6 Khalil and colleagues originally suggested that PP13 was effective in the first trimester marker; however, in a second larger study, PP13 concentrations were not able to predict pre-eclampsia risk until 13 weeks. 7,8 Unfortunately, several studies have suggested that maladaptive trophoblast invasion may already have committed a pregnancy's fate as early as 11 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some authors found no role of the marker at this early stage of pregnancy32, 33. This variation in findings may reflect differences in sample handling, processing and laboratory procedures, making it difficult to compare diagnostic values across different studies34.…”
Section: Discussionmentioning
confidence: 99%
“…Another protein released by the placenta, soluble endoglin (sEng), also has an antiangiogenic role, but acts through a distinct mechanism of sFlt-1 (33). Both trigger endothelial dysfunction and severe preeclampsia (34,35). The placental ischemia, reperfusion and associated oxidative stress amplify apoptosis by rupture of syncytial architecture and promote the release into the maternal circulation of several components (syncytiotrophoblast membrane microparticles and an excess of antiangiogenic factors, such as sFlt-1) that stimulate the synthesis of inflammatory cytokines (36)(37)(38).…”
Section: Pathogenesismentioning
confidence: 99%